Electron impact scattering study on formyl fluoride (HFCO). Issue 18 (January 2020) - Jani, T; Yadav, H; Prajapati, D; Vinodkumar, M; Vinodkumar, P C
Synopsis: Electron impact scattering studies with organic compounds play a significant role in studies related to astrophysics and radiation physics. We present here electron impact scattering studies on formyl fluoride as no cross-sectional data is available to the best of our knowledge. Total scattering cross sections (TCS) on comparing with iso-electronic molecule reveals that at low energy molecular dipole moment plays a significant role in cross-section deviation and at high energy the tendency seems to be same in all the formyl series.